The Continuous Learning Cycle: A Multi-phase Post-occupancy Evaluation (POE) of Decentralized Nursing Unit Design. (April 2022) - Cai, Hui; Spreckelmeyer, Kent
Purpose: This study aims to demonstrate how multiphase postoccupancy evaluation (POE) research was integrated into multiple projects to develop a continuous learning cycle. Background: Despite the well-recognized importance of POE, few studies have reported how knowledge from POE is applied in new designs. Method: This study is developed as a multiphase POE that spanned 3 years and across three units. Phase I POE compared an existing unit (Unit A) in Hospital A and a new Unit B in Hospital B that has implemented innovative design features such as decentralized nurse stations. The idea was to understand the challenges of the existing facility in Hospital A and gather lessons learned from the new design in Unit B to inform the design of the Hospital A expansion (Unit C). After the new expansion was occupied, the Phase II POE was conducted using the same set of POE tools in both Unit C and Unit A. The POE applied the following methods: (1) patient room evaluations using the Center for Health Design standardized POE tools, (2) space syntax analysis of visibility, and (3) a pre- and postmove analysis of Press Ganey data. Results: The results demonstrated that by incorporating lessons learned from the Phase I POE, Unit C has further improvement on patient room design ratings, improved patient satisfaction, and better visibility among nurse work areas compared to Unit A and Unit B. Conclusions: The multiphase, multisite POE with standardized tools has demonstrated its value as an important tool for continuous design quality improvement.